Effect of light spectra on cereal fungal pathogens, a review. (March 2023) - Cerón-Bustamante, M.; Balducci, E.; Beccari, G.; Nicholson, P.; Covarelli, L.; Benincasa, P.
Abstract: Light plays a crucial role in the growth and development of fungi. Fungal photoperception is controlled by several receptors such as phytochromes, cryptochromes/photolyase, opsins, and light oxygen voltage proteins that can trigger specific responses along the light spectrum. Although the filamentous fungus, Neurospora crassa is a leading research model in photoresponse studies, the analysis of a diverse range of fungal species has led to a better understanding of light signals in growth, reproduction, and secondary metabolism in the Fungi kingdom. In fungal pathogens, light has been demonstrated to be crucial during infection, colonization, and for the successful development of plant diseases. In this review, the most recent findings on the photobiology of the best-studied fungal pathogens of cereals are summarized. In particular, the effects of light on the germination, growth, sporulation, pathogenicity, and secondary metabolism of the most important wheat, barley, maize, and rice pathogens are discussed. Highlights: Light influences growth, reproduction, and secondary metabolism in fungi. Fungi sense light via flavin-based proteins, rhodopsins, and phytochromes receptors. Light mainly mediates conidiation, virulence, and mycotoxin production in diverse cereal pathogens. Cereal pathogens photobiology could provide elements for the development of control strategies.